Potential Unconventional Gas Plays in Mature Basin of the Czech Republic - Bujok, Petr; Klempa, Martin; Skupien, Petr; Matýsek, Dalibor; Porzer, Michal (GeoScience Engineering, 2016)
The presence of unconventional resources has been proven in deeper parts of mature oil and gas provinces and coal basins of the World. In this context it is worth to focus also on the prospects of unconventional gas production from within hydrocarbon provinces of Moravian part of the Vienna basin. Estimation of hydrocarbon generation potential of Jurasic marls from the Mikulov Formation of the Czech part of the Vienna Basin was performed based on the Rock Eval pyrolysis.